Inflammatory, Oxidative Stress, and Angiogenic Growth Factor Responses to Repeated-Sprint Exercise in Hypoxia - Kasai, Nobukazu; Kojima, Chihiro; Sumi, Daichi; Ikutomo, Akiho; Goto, Kazushige (Frontiers in Physiology, 2019)
The present study was designed to determine the effects of repeated sprint exercise in moderate hypoxia on inflammatory, muscle damage, oxidative stress, and angiogenic growth factor responses among athletes. Ten male college track and field sprinters [mean ± standard error (SE): age, 20.9 ± 0.1 years; height, 175.7 ± 1.9 cm; body weight, 67.3 ± 2.0 kg] performed two exercise trials in either hypoxia [HYPO; fraction of inspired oxygen (FiO2), 14.5%] or normoxia (NOR; FiO2, 20.9%). The exercise consisted of three sets of 5 × 6-s maximal sprints with 30-s rest periods between sprints and 10 min rest periods between sets. After completing the exercise, subjects remained in the chamber for 3 h under the prescribed oxygen concentration (hypoxia or normoxia). The average power output during exercise did not differ significantly between trials (P = 0.17). Blood lactate concentrations after exercise were significantly higher in the HYPO trial than in the NOR trial (P < 0.05). Plasma interleukin-6 concentrations increased significantly after exercise (P < 0.01), but there was no significant difference between the two trials (P = 0.07). Post-exercise plasma interleukin-1 receptor antagonist, serum myoglobin, serum lipid peroxidation, plasma vascular endothelial growth factor (VEGF), and urine 8-hydroxydeoxyguanosine concentrations did not differ significantly between the two trials (P > 0.05). In conclusion, exercise-induced inflammatory, muscle damage, oxidative stress, and VEGF responses following repeated sprint exercise were not different between hypoxia and normoxia.